DESCRIPTION OF THE DISCIPLINE OF AUTISTIC STUDENTS AT SD SURYO BIMO KRESNO SEMARANG - Fitria, Ana; Abadi, Auliya Rahma; Zahra, Dhafiyah; Masfia, Irma; Fahmy, Zulfa (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2024)
Inclusive education provides opportunities for children with special needs, including children with autism. One important aspect of education is discipline. Autistic children have unique challenges in following and understanding school rules. This article investigates the description of disciplinary behaviors that emerge in autistic children and includes an understanding of the routine of disciplinary behaviors of autistic children at school. This research method uses qualitative procedures. This research was conducted at SD Suryo Bimo Kresno, and the subject was autistic students. Data collection techniques used in this study include checklist observation, documentation, and interviews. Data analysis techniques in this study used data reduction, data presentation, and conclusion drawing. The results of observations show an increase in the discipline of autistic children, such as arriving on time, attending apples in an orderly manner, and being able to do tasks despite having impaired focus. While the results of interviews with accompanying teachers and principals show that the school still applies the applicable rules, there are several waivers for children with special needs. The role of the accompanying teacher is very important in gradually understanding students regarding existing rules to become more disciplined. A disciplined attitude is characterized by a calm reaction during learning, following the roll call, and being able to complete the tasks given by the teacher. The observations and interviews conclude that children with autism at school gradually show progress in discipline.